International competitive analysis of wine producer small and midsize companies on enterprise resource management - Sümegi, Zs.; Molnár, A. (International Journal of Horticultural Science, 2009)
In our research using primary data sources we are searching for satisfactory evidences, that the impressive economical growth of China has a strong impact on Chinese grape and wine production, wine market. However grape cultivation has long tradition in China, modem grape wine and wine production has only started 20 years ago. During my research I have collected the very rare and unreliable information on this theme to make a picture of Chinese grape and wine production. Using primary sources describe the present situation of Chinese grape industry, verify the supposition that the rise of Chinese grape crop land includes the growth of the total size of wine grape plantations. After this verification I make a comparative analysis of Chinese and Hungarian grape cultivation costs, to confirm, that grape and wine producing is a more requital activity in China than in Hungary.